The learning preferences of current generational groups - Quinton, Stephen (Curtin University of Technology, 2005)
Today's computer literate students think in ways that are incompatible with current educational goals and practices. If one of the aims of learning is to provide lifelong benefits for all, then a substantial rethink on the learning needs of students and the goals of education has become paramount. This emergent imperative presents an unfamiliar challenge for educational institutions to examine their past assumptions and to facilitate success in meeting the needs of current and future generations of learners. The type of change proposed in this paper requires a comprehensive rethink not only to devise innovative alternatives to accepted methods and practices, but also to develop theories and pedagogies more attuned to the preferences, values, and attitudes of the technology and information proficient generations. The eventual outcome will be a dramatic transformation in the essential nature and purpose of the online learning environment. It is not just bridging the transition from 'traditional' to 'digitised' learning that is fraught with difficulties. Any attempt to accommodate the skills and learning needs of the current generation computer "literate" will compel education designers to think entirely "outside the box" and consider solutions previously thought impossible. Success in meeting the needs of learners will require radically new teaching methods and strategies. Such strategies may include for example: content interactive features that offer "intelligent" meaningful responses; the ability to annotate and record ideas as required; user generated (manually) and automatically (dynamically generated hyperlinks to alternative materials relative to the current context; and automated display of customised content such as interactive assessments and constructive feedback tailored to students' immediate learning needs. For these innovations to be truly effective, libraries must also be viewed as an essential component of a complex network of information resources. Thus, it is argued that the nature of the learning environment must change dramatically, in particular in relation to the choice of flexible delivery techniques that are supported by distributed computing networks, advanced educational software, and universal access to quality learning resources regardless of location and time.